FETUS’ WEIGHT AND Hb LEVEL WITH APGAR SCORE OF NEWBORN WHO SUFFERS ASPHYXIA AT RSUDP NTB IN 2016 - Aty Sulianty; Syajaratuddur Faiqah (poltekkes kemenkes mataram, 2018)
Abstract: Infant mortality (AKB) is one important indicator in determining the level of public health. Demographic Health Survey Indonesia based estimation of infant mortality (AKB) of 34 per 1000 live births. It is still far from the target of the MDGs, 2015 AKB amounted to 23 per 1000 live births and reports from the World Health Organization, (WHO) in 2012 that each year, approximately 3% (3.6 million) from 120 million infants born experienced asphyxiation. The objective study was to know the relationship of fetus’ weight and Hb levels and APGAR score who suffered asphyxia in RSUDP NTB 2016. The method in this study was Observational Analytic study with Cross Sectional Sample design was 237 newborn baby who suffered asphyxia. The data were analyzed using regression correlation test. The findings in this research indicated that there was a correlation between newborn baby’s body weight and Hb levels with APGAR score who suffered asphyxia at RSUD NTB in 2016 with (P value = 0.01) and shows a weak relationship and patterned a positive value (r = 0,158), (r = 0,206). A suggestion for further research on fetus’ Hb levels and APGAR score with different research design and set the sample criteria relate to factors of pregnancy and labor.Keywords: Newborn Weight, Fetus’ Hb Levels, Apgar score, Asphyxia.